Strengthening self-efficacy in the application of health protocols to increase work productivity during pandemic in manufacturing industry - Sifai, Izzatul Alifah (BKM Public Health and Community Medicine, 2021)
Objective: The International Labor Organization (ILO) assesses that manufacture is one of the sectors that has a high risk of operating during a pandemic. The characteristics of manufacturing, namely the production process that cannot be done remotely and the relatively low quality of human resources, makes manufacturing at high risk when operating during this pandemic. Working in stressful situations such as the threat of termination of employment and the threat of COVID-19 itself causes disruption to labor productivity. Content: One aspect of increasing work productivity during this pandemic is by increasing self-efficacy in implementing health protocols. Several recommendations based on previous research formulate that management needs to review the implementation of several interventions to increase self-efficacy, including the provision of health protocol infrastructure, health promotion, dissemination of reliable information, designing mental health and stress management programs, and providing full support to workers. These efforts are expected to be able to increase labor productivity and maintain a safe work environment.